A Pragmatic Randomized Controlled Trial to Increase PrEP Uptake for HIV Prevention: 55-Week Results From PrEPChicago. (1st January 2021) - Schneider, John A.; Young, Lindsay; Ramachandran, Arthi; Michaels, Stuart; Cohen, Hildie; Robinson, Ishida; Alon, Leigh; Hill, Brandon; Nakasone, Sarah; Balenciaga, Mario; Motley, Darnell; Bouris, Alida; et al.
Abstract : Objectives: We tested preliminary efficacy of a peer change agent type I network intervention to increase pre-exposure prophylaxis (PrEP) linkage to care among network members connected to young Black men who have sex with men. Design: Parent study is a pragmatic randomized controlled trial with 110 weeks of total follow-up. Interim midpoint analyses are performed here using participant data before crossover assignment at 55 weeks. Methods: We randomly assigned 423 participants in Chicago to receive the network intervention, an opinion leader workshop with telephonic booster sessions, versus a time-matched control from 2016 to 2018. The consolidated surrogate outcome was PrEP referral and linkage to clinical care among network members connected to study participants and was collected from independent administrative data. Results: Each study participant in the trial (n = 423) had on average 1822 network contacts who could be eligible for PrEP referral and linkage. During the 55-week observation period, PrEP referral was most likely to occur within 3 days of an intervention session compared to control [odds ratio (OR) 0.07 (0.02–0.013); P = 0.007] resulting in 1–2 referrals of network members per session. Network members with referral or linkage were more likely to be connected to study participants in the intervention arm than the control condition [aOR 1.50 (1.09–2.06); P = 0.012]. Conclusions: A peer change agent type I network intervention is preliminarily effective at diffusing PrEP through a network of individuals highly susceptible to HIV over 55 weeks. This low-intensity intervention demonstrated network-level impact among populations that have experienced limited PrEP care engagement in the United States. Abstract : Supplemental Digital Content is Available in the Text.